The Redistributional Effects of Inflation - Bach, G. L.; Ando, Albert (The Review of Economics and Statistics, 1957)
HOW important is it to avoid a moderate, creeping inflation? When nearly full employment has been reached, should continued pressure for higher employment be applied even at the cost of inflationary results? If inflationary pressures exist, what repressive measures are justified to offset these pressures? In spite of widespread agreement on the general objectives of monetary-fiscal policy, we have little organized information on the effects of inflation on different groups in periods of substantially full employment. We need to know more in detail about these effects in order to make reasoned judgments as to how hard we should fight against such inflation and what particular types of repressive policies are best to use. Most major American groups appear to be against inflation. President Eisenhower and ex-President Truman, the C.I.O. and the A.F. of L., the National Association of Manufacturers and the Committee for Economic Development, all have stressed the importance of preserving the purchasing power of the American dollar. Avoidance of mass unemployment and depression seems definitely the first objective of governmental monetary-fiscal policy, but avoidance of inflation appears to come not far behind. Yet the reasons why these diverse groups oppose inflation, if we are to judge by the statements of their leaders, are many, and often muddled. Nor is there any clear consensus among economists as to who gains and who loses from inflation. The most common statements we have found by leading economists 1 fall into two groups: lead-lag propositions, notably that wages lag behind profits in inflation, while interest and rents lag still further, reflecting varying degrees of upward price flexibility; and debtor-creditor propositions, notably that debtors gain at the expense of creditors in inflation. The present investigation suggests that these lead-lag propositions about inflation are questionable, if not wrong, as applied to the type of inflation in the United States since I939. And while there has indeed been a mass debtorcreditor inflation-induced transfer of purchasing power in the United States since I939, the pattern of the transfer has been complex. Business firms, often thought to be major debtors in the American economy, have not been major gainers from inflation on debtor account. This exploratory paper is concerned primarily with the redistributional effects of the recent moderate American inflation on current incomes and on wealth. It does not consider directly the effect inflation may have on aggregate output and employment, although the findings may be helpful in analyzing this question. The following sections include: (I) a brief statement of our approach in investigating the problem; (II) some evidence concerning the effect of inflation on the distribution of income by economic function; (III) an analysis of the transfer of wealth by inflation; and (IV and V) brief consideration of inflation's effects on different classes of households and on nonfinancial corporations, respectively. For those already familiar with the behavior of shares of the national income over the years considered, the later sections of the paper will be of primary interest.